(untitled) (Journal on studies and research of academic knowledge, 2022)
The research is developed in a time with unprecedented characteristics due to the pandemic situation that impacts the country and the whole world; and, in this area, the situational analysis is carried out with the purpose of providing a diagnosis on the research at the National University of Itapúa (UNI) and as an action-contribution of the research, update the virtual repository of the UNI´s Library, which aims is to accompany the process for quality assurance of higher education and overcome negative effects that the lack of reliable and accessible scientific information produces on the quality of education. The study is phenomenological, natural, case study type, non-experimental cross-sectional design, qualitative approach. The unit of analysis is the UNI, the universe of study is the academic units and the Research and Environment Directorate (DIA). The relevant results denote that at UNI and in all academic units, the regulatory framework is formally established in terms of declared policies, plans, programs, as well as in the Mission and Vision. The research development structure at UNI is sufficient, there is a need for a larger budget for the knowledge production process, researchers training, incentives and programs which count with a financial backing. Relevance: enabling a virtual space in the UNI Library, with proven scientific validity. Influencing factors: relevance of investigations concluded with the areas of knowledge, lack of motivation among teaching professionals towards scientific production, need to manage with an innovative approach. The achievement of the strategic objectives established for research at UNI is in process; improvement plans foresee positive actions. The UNI scientific repository is updated with the management and incorporation of thirty (30) research conducted in the years 2018 and 2019, classified by area of science.